Improved solution for node location multilateration algorithms in wireless sensor networks. Issue 13 (1st June 2016) - Müller, C.; Alves, D.I.; Uchôa‐Filho, B.F.; Machado, R.; de Oliveira, L.L.; Martins, J.B.S.
Abstract : A modification of the gradient descent method that can be used in multilateration algorithms for node location in wireless sensor networks (WSNs) is proposed. Through computer simulations, the proposed solution compares favourably in terms of computational complexity and convergence performance with respect to a multilateration method based on the Gauss–Newton algorithm is shown, which is commonly used for this purpose. The contribution can be useful for multilateration tasks in real applications based on WSN that have hardware and/or power constraints.